Ocean acidification alters bacterial communities on marine plastic debris. (December 2020) - Harvey, Ben P.; Kerfahi, Dorsaf; Jung, YeonGyun; Shin, Jae-Ho; Adams, Jonathan M.; Hall-Spencer, Jason M.
Abstract: The increasing quantity of plastic waste in the ocean is providing a growing and more widespread novel habitat for microbes. Plastics have taxonomically distinct microbial communities (termed the 'Plastisphere') and can raft these unique communities over great distances. In order to understand the Plastisphere properly it will be important to work out how major ocean changes (such as warming, acidification and deoxygenation) are shaping microbial communities on waste plastics in marine environments. Here, we show that common plastic drinking bottles rapidly become colonised by novel biofilm-forming bacterial communities, and that ocean acidification greatly influences the composition of plastic biofilm assemblages. We highlight the potential implications of this community shift in a coastal community exposed to enriched CO2 conditions. Graphical abstract: Unlabelled Image Highlights: Plastic will act as a novel ecological habitat for microbial communities. Plastics harbour taxonomically distinct microbial communities ("Plastisphere"). Ocean acidification greatly influences the Plastisphere community composition.